Development Of Papaya Leaf Extract/Pva-Based Nanofibers Using Electrospinning Method For Medical Appliaction as A Wound Dressing - Brahma Jesayas Bua; Melvia Natalia Aponno; Marissa Gloryanti Soplanit; Ervina Rumpakwakra (Jurnal Riset Kefarmasian Indonesia, 2026)
The nanofiber manufacturing process is carried out using the electrospinning method, which produces nanometer-sized fibers. This study used a mouse test animal model, where wounds in mice were treated with papaya leaf extract/PVA nanofibers, then compared with a control group using commercial wound dressings. Evaluation was carried out based on wound healing parameters, such as the speed of wound closure and the ability to form an inhibition zone on E. Coli bacteria. Based on the results of SEM testing, it was seen that the morphology of papaya leaf extract/PVA nanofibers had been successfully synthesized with the formation of fibers. The results of observations for the inhibition of E. Coli bacteria for extract concentrations of 5% and 10% for 7 and 24 hours were 13.33 and 12.43 mm. The application of 10% papaya leaf extract/PVA nanofibers was then tested as a wound dressing on test animals (mice). The results showed that after 9 days, 10% papaya leaf extract/PVA was able to accelerate wound healing in mice. Overall, this research can contribute to the development of nanotechnology-based wound dressing materials that utilize natural resources for medical applications.